Is arbitrage tying the price of ethanol to that of gasoline? Evidence from the uptake of flexible-fuel technology - Alberto Salvo; Christian Huse; Sergio Goldbaum; Fernanda Lima (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2007)
As much of the world goes searching for alternative sources of energy to oil, Brazil's three-decade experience in developing a successful substitute for gasoline merits attention. Brazil is the only sizable economy to date to have developed a ubiquitously distributed alternative to oil-based fuels in road transportation: ethanol from sugarcane. Perhaps unsurprisingly, the uptake of flexible-fuel (dual-fuel) vehicle technology has been tremendous. We provide a stylized model of the vertical sugar industry which incorporates arbitrage by producers, across domestic and export markets for ethanol and sugar, and arbitrage by consumers, across ethanol and gasoline at the pump. We show that the model stands up well to the empirical covariation in prices over 30 years. In particular, owing to the increasing penetration of flexible-fuel vehicles, consumer arbitrage is tying the retail price of ethanol to that of gasoline. Of relevance to the current food-versus-fuel debate, the outward shift of the ethanol demand curve, at price levels where traditional gasoline consumers arbitrage, may lead to higher sugar prices, thanks to substitution in demand (gasoline and ethanol) and in supply (sugar and ethanol).
Keywords: F19; 330; Ethanol; gasoline; sugar; biofuels; food prices; commodity prices; food-versus-fuel debate; arbitrage; export price floor; price convergence; flexible-fuel vehicles; Biokraftstoff; Produktsubstitution; Benzin; Preiselastizität; Brasilien